31 Head home: a prospective cohort study of a nurse led paediatric head injury clinical decision tool at a district general hospital. Issue 12 (23rd November 2020) - Aldridge, Patrick; Castle, Heather; Russell, Emma; Phillips, Clare; Guerrero-Luduena, Richard; Rout, Raj
Abstract : Aims/Objectives/Background: Objectives: To assess if application of a nurse-led paediatric head injury clinical decision tool would be safe compared to current practice. Background: >700, 000 children attend UK hospitals' each year with a head injury. Research indicates <1% undergo neurosurgical intervention. No published evidence for nurse-led discharge of paediatric head injuries exists. Methods/Design: Methods – All paediatric (<17 years) patients with head injuries presenting to our Emergency department (ED) 1st May to 31st October 2018 were prospectively screened by a nurse using a mandated electronic 'Head Injury Discharge At Triage' questionnaire (HIDATq). We determined which patients underwent computed tomography (CT) brain and whether there was a clinically important intracranial injury or re-presentation to ED. The negative predictive value of the screening tool was assessed. We determined what proportion of patients could have been sent home from triage using HIDATq. Results/Conclusions: Results - Of 1739 patients screened; 61 had CTs performed due to head injury (6 abnormal) with a CT rate of 3.5% and 2% re-presentations. Of the entire cohort, 1052 screened negative. 1 CT occurred in this group showing no abnormalities. Of those screened negative: 349/1052 (33%) had 'no other injuries' and 543/1052 (52%) had 'abrasions or lacerations'. HIDATq's negative predictive value for CT was 99.9% (95% Confidence interval (CI) 99.4–99.9%) and 100% (CI 99.0–100%) for intracranial injury. The positive predictive value of the tool was low. Five patients screened negative and re-presented within 72hrs but did not require CT imaging. Conclusion - A negative HIDATq appears safe in our ED. Potentially 20% (349/1739) of all patients with head injuries presenting to our department could be discharged by nurses at triage with adequate safety netting advice. This increases to 50% (543/1739) if patients with lacerations or abrasions were treated and discharged at triage. A large multi-centre study is required to validate the tool.